Psychometric validation of the Polish version of the Central Sensitization Inventory in subjects with chronic spinal pain - Kosińska, Barbara; Tarnacka, Beata; Turczyn, Paweł; Gromadzka, Grażyna; Malec-Milewska, Małgorzata; Janikowska-Hołowenko, Dorota; Neblett, Randy (BMC neurology, 2021)
Central sensitization is an amplification of neuronal signaling within the central nervous system. The Central Sensitization Inventory was introduced in 2012. A Polish version of the CSI (CSI-Pol) was developed in 2019, but it was not psychometrically validated. The aim of this study was to validate the CSI-Pol in a sample of Polish-speaking patients with chronic spinal pain and compare them with a group of healthy control subjects. The CSI-Pol was administered to 151 patients with chronic spinal pain recruited from two centers. It was re-administered 7 days later. The psychometric properties were then evaluated, including test-retest reliability, construct validity, factor structure and internal consistency. We correlated the CSI-Pol with functional scales, depression and social support scales and compared CSI-Pol scores in the clinical subjects with 30 healthy control subjects recruited from medical staff and their families. The CSI-Pol demonstrated excellent internal consistency (Cronbach's α =0,933) and test-retest reliability (Intraclass Correlation Coefficients - ICC =0.96), as well as significant positive associations with other patient-reported scales, including the Neck Disability Index (r = 0.593), Revised Oswestry Low Back Pain Disability Questionnaire (r = 0.422), and other measures of functional and depressive states. An exploratory factor analysis resulted in a 4-factor model. CSI-Pol scores in the clinical sample (35.27 ± 17.25) were significantly higher than the control sample (23.3 ± 8.9). The results of this study suggest that the CSI-Pol may be a useful clinical tool for assessing central sensitization related symptoms and guiding appropriate treatment in Polish-speaking patients with spinal pain.